Best Practice “HOTS – Home Stay” Encouraging Students’ HOTS through Home Stay Activities - Arjus Putra (English Language Teaching and Research, 2018)
There are a lot of model schools constructed by goverment and as well as by private. Those schools significantly contribute toward the quality progress of education in social’s eyes. For English subject side students from model schools may achieve very good score but as phenomena that they can not prove their excellency in English for direct communication. This happened as the impact of teaching and learning only focused on LOTS (Lower Order Thingking) based. To overcome this problem that teaching and learning English must also focus on HOTS or Higher Order Thinking Skills.This is the background of HOTS – Home Stay to encourage students’ Higher Order Thinking Skills is excecuted. This activity is conducted in the form of English out door activity. This has been conducted since 2007 in several places. The activity focused on learning by doing with HOTS approached.Finding from HOTS – Home Stay activity is that students grow in their interest and motivation for using English communication. Then their thinking quality is also increase especially for “analysis, synthesis and evaluation”. As these three words are part of taxonomy bloom for higher order thinking skills level. HOTS – Home stay activity is recommended for the English teachers of Junior High Scool and Senior High Shcool to desigh the activity of HOTS – Home Stay for students. Keyword: Home Stay, HOTS, Outdoor,